1998
DOI: 10.1128/jvi.72.1.497-503.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Viral Spike Protein Is Not Involved in the Polarized Sorting of Coronaviruses in Epithelial Cells

Abstract: Coronaviruses are assembled by budding into a pre-Golgi compartment from which they are transported along the secretory pathway to leave the cell. In cultured epithelial cells, they are released in a polarized fashion; depending on the virus and cell type, they are sorted preferentially either to the apical domain or to the basolateral plasma membrane domain. In this study, we investigated the role of the coronavirus spike protein, because of its prominent position in the virion the prime sorting candidate, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Furthermore, M protein glycosylation was also shown not to be critical for interaction with the S protein (de Haan et al, 1999). These observations are consistent with studies that used tunicamycin (Rossen et al, 1998;Stern and Sefton, 1982) and monensin (Niemann et al, 1982) to inhibit glycosylation in infected cells.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, M protein glycosylation was also shown not to be critical for interaction with the S protein (de Haan et al, 1999). These observations are consistent with studies that used tunicamycin (Rossen et al, 1998;Stern and Sefton, 1982) and monensin (Niemann et al, 1982) to inhibit glycosylation in infected cells.…”
Section: Introductionsupporting
confidence: 86%
“…In contrast, the M protein released from cells infected with Alb244 or Alb246 migrated in the gel as a single band with approximately the same electrophoretic mobility as the unglycosylated M protein species released from Alb138-or Alb139-infected cells. The M proteins released from cells infected with Alb248 or Alb250 appeared as a smear in the gel, quite similar to the M proteins from group I coronaviruses, which carry Nlinked sugars (Rossen et al, 1998;Vennema et al, 1990). The appearance of the M proteins as a smear in the gel is probably the result of extensive, heterogeneous modifications of the sugar side chains.…”
Section: Analysis Of Viral Proteinsmentioning
confidence: 76%
“…We previously showed that coronavirus S glycoproteins are densely decorated by heterogeneous N-linked glycans protruding from the trimer surface (Walls et al, 2016b;Walls et al, 2019;Xiong et al, 2018). These oligosaccharides participate in S folding (Rossen et al, 1998), affect priming by host proteases (Yang et al, 2015b), and might modulate antibody recognition (Pallesen et al, 2017;Walls et al, 2019). SARS-CoV-2 S comprise 22 N-linked glycosylation sequons per protomer and oligosaccharides are resolved in the cryo-EM map for 16 of these sites (Figure 4).…”
Section: Sars-cov-2 Recognizes Hace2 With Comparable Affinity To Sarsmentioning
confidence: 97%
“…As the coronavirus S glycoprotein is surface-exposed and mediates entry into host cells, it is the main target of neutralizing antibodies (Abs) upon infection and the focus of therapeutic and vaccine design. S trimers are extensively decorated with N-linked glycans that are important for proper folding (Rossen et al, 1998) and for modulating accessibility to host proteases and neutralizing Abs (Walls et al, 2016b;Walls et al, 2019;Xiong et al, 2018;Yang et al, 2015b). We previously characterized potent human-neutralizing Abs from rare memory B cells of individuals infected with SARS-CoV (Traggiai et al, 2004) or MERS-CoV (Corti et al, 2015) in complex with SARS-CoV S and MERS-CoV S to provide molecular-level information of the mechanism of competitive inhibition of S B attachment to the host receptor .…”
Section: Introductionmentioning
confidence: 99%
“…For example, although measles virus glycoproteins H and F are transported in a random fashion or to basolateral membrane, respectively, virus budding occurred predominantly from the apical surface of polarized MDCK cells (Maisner et al, 1998). Similarly, the spike protein of coronavirus is not involved in the polarized budding of this virus (Rossen et al, 1998). Moreover, Marburg virus buds predominantly from the basolateral surface, while its glycoprotein is transported to the apical surface (Sanger et al, 2001).…”
Section: Selection Of the Budding Sitementioning
confidence: 99%